Evaluation of free radical scavenging and immunostimulant activities of water soluble polymeric substances from Cinnamomum zeylanicum bark - Kaur, Navdeep (My University, 2016)
Cinnamomum zeylanicum is a commonly used spice with many medicinal properties but not much scientific data is available on bioactive properties of water soluble polymeric substances of Cinnamomum. Hence, in the present study, free radical scavenging and immunostimulating effects of water soluble polymeric substances evaluated. Chemical analysis of polymeric substances confirm the presence of protein and the polysaccharide contents was found to be 250 μg/mg taking glucose as standard. DPPH assay results shows that free radical scavenging activity of polymeric extract increased with concentration and Further MTT assay were carried out to study the effect of extract on growth of unstimulated and concanavalin A stimulated peripheral blood mononuclear cells (PBMCs). It has been observed that 500 and 1000 μg/ml of polymeric substances induce the proliferation of both unstimulated and stimulated PBMCs which suggest the immune stimulating activity. Present study suggest that Cinnamomum zeylanicum possess bioactive water soluble polymeric substances which has the potential to be used for medicinal purpose.
Keywords: Cinnamomum Zeylanicum; Free radical scavenging activity; Immunostimulant activity